Emerging stability of forest productivity by mixing two species buffers temperature destabilizing effect. Issue 11 (18th August 2022) - del Río, Miren; Pretzsch, Hans; Ruiz‐Peinado, Ricardo; Jactel, Hervé; Coll, Lluís; Löf, Magnus; Aldea, Jorge; Ammer, Christian; Avdagić, Admir; Barbeito, Ignacio; Bielak, Kamil; Bravo, Felipe; et al.
Abstract: The increasing disturbances in monocultures around the world are testimony to their instability under global change. Many studies have claimed that temporal stability of productivity increases with species richness, although the ecological fundamentals have mainly been investigated through diversity experiments. To adequately manage forest ecosystems, it is necessary to have a comprehensive understanding of the effect of mixing species on the temporal stability of productivity and the way in which it is influenced by climate conditions across large geographical areas. Here, we used a unique dataset of 261 stands combining pure and two‐species mixtures of four relevant tree species over a wide range of climate conditions in Europe to examine the effect of species mixing on the level and temporal stability of productivity. Structural equation modelling was employed to further explore the direct and indirect influence of climate, overyielding, species asynchrony and additive effect (i.e. temporal stability expected from the species growth in monospecific stands) on temporal stability in mixed forests. We showed that by adding only one tree species to monocultures, the level (overyielding: +6%) and stability (temporal stability: +12%) of stand growth increased significantly. We identified the key effect of temperature on destabilizing stand growth, which may be mitigated by mixing species. We further confirmed asynchrony as the main driver of temporal stability in mixed stands, through both the additive effect and species interactions, which modify between‐species asynchrony in mixtures in comparison to monocultures. Synthesis and applications . This study highlights the emergent properties associated with mixing two species, which result in resource efficient and temporally stable production systems. We reveal the negative impact of mean temperature on temporal stability of forest productivity and how the stabilizing effect of mixing two species can counterbalance this impact. The overyielding and temporal stability of growth addressed in this paper are essential for ecosystem services closely linked with the level and rhythm of forest growth. Our results underline that mixing two species can be a realistic and effective nature‐based climate solution, which could contribute towards meeting EU climate target policies. Abstract : This study highlights the emergent properties associated with mixing two‐species, which result in resource efficient and temporally stable production systems. We reveal the negative impact of mean temperature on temporal stability of forest productivity and how the stabilizing effect of mixing two species can counterbalance this impact. The overyielding and temporal stability of growth addressed in this paper are essential for ecosystem services closely linked with the level and rhythm of forest growth. Our results underline that mixing two species can be a realistic and effective nature‐based climate solution, which could contribute towards meeting EU climate target policies. Resumen: Las cada vez más frecuentes perturbaciones en masas forestales monoespecíficas en todo el mundo, son una muestra de su inestabilidad bajo el cambio climático. Numerosos estudios indican que la estabilidad temporal de la productividad aumenta con la riqueza de especies, aunque los fundamentos ecológicos de esta relación se han estudiado principalmente en experimentos de diversidad de especies. Para una gestión adecuada de los ecosistemas forestales, es necesaria una mejor comprensión del efecto de la mezcla de especies en la estabilidad temporal de la productividad y de cómo esta se ve modificada por las condiciones climáticas. En este trabajo usamos una base de datos única de 261 masas monoespecíficas y mixtas de dos especies a largo de un amplio rango de condiciones climáticas para examinar el efecto de la mezcla de especies en el nivel y estabilidad temporal de la productividad. Las mezclas estudiadas son combinaciones de dos especies entre cuatro de las especies forestales más relevantes en Europa. Se utilizan modelos de ecuaciones estructurales para explorar la influencia directa e indirecta del clima, el mayor crecimiento en mixtas que en puras ( overyielding ), la asincronía entre especies y el efecto aditivo (estabilidad temporal esperada según el crecimiento de las dos especies en las masas puras) en la estabilidad temporal en masas mixtas. Los resultados muestran que añadiendo solo una especie a las masas monoespecíficas el nivel ( overyielding : +6%) y la estabilidad temporal (+12%) del crecimiento aumentan significativamente. Se ha identificado que la temperatura tiene un efecto clave en la desestabilización del crecimiento, que puede ser mitigado en parte por la mezcla de especies. Se confirma que la asincronía, a través del efecto aditivo y de la interacción de especies (que modifica la asincronía entre especies en masas mixtas con respecto a la de las masas monoespecíficas), es el principal factor que explica la mayor estabilidad temporal en masas mixtas. Síntesis y aplicaciones. Este estudio revela las propiedades emergentes asociadas a la mezcla de dos especies, que resultan en sistemas de producción eficientes y estables. Se identifica el impacto negativo de las temperaturas en la estabilidad temporal de la productividad y cómo el efecto estabilizador de la mezcla de dos especies puede contrarrestar este impacto. El nivel y la estabilidad temporal del crecimiento estudiados en este trabajo son fundamentales en los servicios ecosistémicos ligados al nivel y el ritmo del crecimiento forestal. Los resultados subrayan que la mezcla de dos especies puede ser una realista y efectiva solución climática basada en la naturaleza, que contribuya a cumplir los objetivos climáticos de la EU.